Premenstrual symptoms and associated factors in female students in Saudi Arabia: a cross-sectional study - Rani, Vanitha Innocent; Saikannan, Akshaya; Aseeri, Abeer S.; Meawad Elsayed, Eman Baleegh; Ahmed Moawad, Gehan EL Nabawy; Ahmed Abdelgawwad, Rasha Gamal; Chellathurai, Amutha; Nasrin Nisha, Kamaldeen; Abd El-Maksoud, Mona M.; Shattla, Safaa Ibrahem; Rajappa, Francis Moses (Frontiers in Public Health, 2025)
BackgroundPremenstrual syndrome (PMS) is a common condition affecting the physical, psychological, and behavioral health of reproductive-aged women. This study aimed to assess the association between sociodemographic and menstrual characteristics and the severity of PMS symptoms among female students.MethodsA cross-sectional study was conducted among 370 female college students. Data were collected through a structured questionnaire covering sociodemographic factors, menstrual characteristics, and PMS symptoms across three domains: physiological, psychological, and behavioral. Descriptive statistics, ANOVA, and multiple linear regression analyses were performed to identify associated factors.ResultsDepartments (94.6%). The majority had a normal BMI (65.4%), and 76.5% reported moderate menstrual flow. ANOVA results indicated significant associations between PMS symptoms and BMI, marital status, menstrual cycle length, and menstrual flow. In the regression models, overweight or obese students demonstrated significantly lower physiological (β = −0.283, p = 0.031), psychological (β = −0.348, p = 0.018), and behavioral symptom scores (β = −0.481, p < 0.001) compared with underweight peers. Students with heavy menstrual flow reported higher symptom scores across all domains (physiological: β = 0.931, p < 0.001). Overweight or obese students exhibited lower symptom scores compared to their underweight peers (β = −0.283, p = 0.031). Additionally, students from non-healthcare departments demonstrated significantly higher psychological symptoms (β = −0.744, p = 0.001), and those who experienced early menarche (≤13 years) showed more behavioral symptoms (β = 0.424, p = 0.013) than healthcare students.ConclusionPMS symptoms among female students are significantly influenced by BMI, menstrual flow characteristics, department of study, and age at menarche. These findings highlight the importance of targeted health education and support programs that consider these factors to effectively manage PMS symptoms in this population.